Host Plants of Mealybugs With Their Damage Extent on Some Selected Plants (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Abstract not availableJ. Asiat. Soc. Bangladesh, Sci. 46(2): 201-207, December 2020